Black tea differs from green tea: it suppresses long-term memory formation in Lymnaea - Zhang, Jack (Commun Integr Biol, 2018)
Foods, such as Green tea (GT), containing the flavonol, (-)-Epicatechin (Epi), enhance the formation of long-term memory (LTM) when snails are operantly conditioned in that substance. That is, a single 0.5 h training session results in LTM; whereas similar training in pond water does not result in LTM. It was of interest to determine if Black tea (BT), which is a more popular beverage than GT and which is derived from the same tea leaves, also enhances LTM formation. We found that BT, unlike GT, depressed homeostatic aerial respiratory behaviour and obstructed LTM formation. We used two different methods to determine if BT altered LTM formation and both procedures showed us that BT obstructed LTM formation. We conclude that BT obstructs LTM formation and depresses homeostatic aerial respiration